Fenomén shrinking cities - Schmeidler, Karel (Lidé města, 2014)
Classic approaches of urban planning are associated with the development of cities, with their growth, their increase and their enlargement. This, however, is no longer the norm. Current demographics show significant changes and movement in economic structures and in suburban areas, often leading to shrinking cities and to changes in their quality. This phenomenon, more and more regularly labelled as Urban Shrinkage, presents new challenges for urbanism theories and for urban planning. Are we ready to accept them? At the beginning of the 21st century, this phenomenon resulting in the shrinking of metropolises is generally spreading throughout Europe. One of the most difficult tasks for European urban planners in the near future will be successfully dealing with the results of the demographic, the economic and the physical processes of narrowing and planning smaller, yet still liveable future metropolises.